Mapping sustainability transitions in contemporary culture - Marat-Mendes, T. (2019)
This presentation draws from research conducted at an ongoing project, ‘SPLACH – Spatial Planning for Change’, which aims to inform a sustainability transition of the Lisbon Metropolitan Area urban planning, towards an improved food system, responding to contemporary cultural concerns. But where does contemporary culture really stand with respect to sustainability? Among many contenders for supplanting postmodernism, we would emphasize hypermodernism, digimodernism, metamodernism and transmodernism, since in many respects, these paradigmatic views are engaged with a sustainability transition. Here, we assess how history, technology and visual culture are valued in contemporaneity. This is done by intersecting our readings of cultural paradigms with key ideas about sustainability, drawn from the SPLACH literature review. Moreover, we highlight opportunities for urban design to accomodate a change towards sustainable urban environments.